Wanprestasi Pinjaman Kredit antara PT. Trust Finance Indonesia dengan PT. Bunga Daru (Studi Putusan Nomor 378/Pdt.G/2024/PN Jkt.Pst) - Maharani, Aurelia Gisa; Pongsirinding, Fisa Ande; Putri, Rafirstka Madyah; Garanta, Sandriani (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
A breach of contract occurs when one of the parties to an agreement fails to carry out their end of the agreement they made. This infraction could be the consequence of negligence, a delay, or a substantive breach of the contract that affects the other party. This study aims to examine the types of contract violations in investment financing for sale-purchase and leaseback agreements, the factors the court considers when rendering a decision, and the resulting legal consequences for the parties involved in the dispute. In this study, a normative juridical approach is taken. This approach includes examining relevant laws and regulations, literature evaluations, and judicial rulings. According to the study's findings, PT. Bunga Daru, the defendant in this case, was found to have violated the terms of the contract by neglecting to make the agreed-upon installment payments for the car loan. The plaintiff’s evidence, which included the defendant’s past late payments and lack of good faith in paying the outstanding debt, was taken into consideration by the panel of judges. The court’s decision mandated that the defendant pay IDR 188,609,521.00 (one hundred eighty-eight million six hundred nine thousand five hundred twenty-one rupiahs) in fines and the remaining loan balance. To ensure the ruling’s enforcement, the court also ordered a security seizure of the car offered as collateral. However, the judges denied the plaintiff’s request for an immediate implementation of the ruling (uitvoerbaar bij voorraad) and a coercive monetary penalty (dwangsom). The court reasoned that the decision must be carried out in accordance with the relevant legal procedures without subjecting the defendant to more pressure.